Stage-specific transcriptomic analysis reveals insights into the development, reproduction and biological function of allergens in the European house dust mite Dermatophagoides pteronyssinus - José Cristian Vidal-Quist; Félix Ortego; Bart N. Lambrecht; Stephane Rombauts; Pedro Hernández-Crespo (BMC Genomics)
Abstract Background House dust mites (HDMs) such as Dermatophagoides pteronyssinus are major allergy elicitors worldwide, yet their gene expression across developmental stages remains underexplored. Herein, we report a comprehensive RNAseq analysis of larvae, nymphs, and adult males and females, mapped to a recently published high-quality genome with extended functional annotations. Results Analysis of differentially expressed genes (DEG) revealed that female-biased expression was the most prevalent profile (16% of genes), while males exhibited the highest fold-change differences. DEG data, combined with network clustering and functional enrichment analysis, highlighted distinct genes and biological processes for each stage and sex: females showed upregulation of genes related to cell division and oogenesis, with vitellogenins among the most abundant transcripts; males exhibited increased expression of genes encoding putative seminal fluid proteins (e.g. endopeptidases, serpins, antimicrobial peptides), and those involved in reproductive regulation (e.g. testis-specific serine kinases); while juveniles displayed enhanced expression of genes related to energy metabolism and growth. Further analysis of endocrine pathways revealed non-canonic mechanisms compared to insect models, particularly in ecdysteroid and sesquiterpenoid biosynthesis and regulation. Expression patterns in genes involved in cuticle formation were also identified, reflecting their role in developmental transitions and sexual differentiation. Allergen and allergen-related gene expression showed an overall increase in feeding juveniles, as well as sex-biased expression, with Der p 27 upregulated in females. These findings provide insight into the physiological roles of allergens in digestion, immunity, and muscle formation, among other functions. Additionally, seven new horizontally transferred genes, including a DNA-repair photolyase linked to females, and novel multigene families (e.g. 119 male-specific beta-propeller proteins, 70 hypothetical cuticular proteins, 23 tetraspanin-like proteins, 5 female-associated putative odorant-binding proteins) were identified. Conclusions This study provides the first genome-wide transcriptomic analysis of a HDM across life stages and sexes, expanding our understanding of the molecular mechanisms underlying mite development, sexual reproduction, and allergen expression. The generated data, fully available via supplementary spreadsheet and the ORCAE online platform, provide a valuable foundation for future allergy research and the development of new mite control strategies.